Detoxification of mustard gas, nerve agents and simulants by peroxomolybdate in aqueous H2O2 solution: Reactive oxygen species and mechanisms. Issue 5 (October 2020) - Zhao, Sanping; Zhu, Yongbing; Xi, Hailing; Han, Mengwei; Li, Daxue; Li, Yang; Zhao, Hongjie
Graphical abstract: Abstract: To overcome the insufficient understanding of the detoxification mechanisms of Chemical Warfare Agents (CWAs) and simulants by a molybdate-activated hydrogen peroxide solution (MoO4 2− -H2 O2 ), detoxification performances toward CWAs and simulants were tested. The detoxification efficacy toward mustard gas (HD), nerve agent GD and VX by using MoO4 2− -H2 O2 was higher than that by using H2 O2 activated/modified by sodium hydroxide, ammonia, bicarbonate, and borates, but the vesicant mustard sulfone (HDO2 ) was only formed when using MoO4 2− -H2 O2 to detoxify HD. Although Reactive Oxygen Species (ROS) such as singlet oxygen ( 1 O2 ), superoxide anion (O2 − ), H2 O2 and peroxide anion (OOH − ) were detected by electron spin resonance (ESR) and chemiluminescence (CL) in the 0.1 M MoO4 2− -1.0 M H2 O2 solution, 95 Mo NMR indicated that Mo(O2 )4 2− was the dominant oxidant for the oxidation of sulfide to sulfoxide and then to sulfone. Oxidation of HD by Mo(O2 )4 2− occurred on the HD-drop/water interface through a direct oxygen transfer mechanism without the participation of H2 O molecules, and further oxidation of HD to HDO2 was inevitable in an aqueous MoO4 2− -H2 O2 solution. 18 O tracer experiments confirmed that OOH − -based perhydrolysis dominated the detoxification reaction of nerve agents in an alkaline H2 O2 solution. Considering the balance of oxidation/nucleophilic reactivity for a practical decontaminant, pH 10.5–11 range was recommended as the ideal for the MoO4 2− -H2 O2 system to detoxify CWAs.